The Feminist Analysis of Shirley Jacksonâ€™s The Lottery; A Dominant-Discourse-Control Framework - Maasoum, Seyed Mohammad Hosseini; Davtalab, Hoda; Vahdati, Mahnoosh (Richtmann Publishing, 2012)
Feminism, originating in late 19th century, is a cover term for a series of movements which seek to define, establish and defend equal rights for women. It focuses on the women's issues and their problems in the society and aims at overcoming their problems. In the three main waves of feminism, many feminists such as Virginia Wolf, Simone de Beauvoir, and Kate Millet aired their views in their popular and famous books. This article deals with the application of feminist criticism to The Lottery by Shirley Jackson, considering Simone de Beauvoir's ideas based on her Second Sex. Many sentences and phrases are quoted through the article to illustrate the women's weakness and the men's power, the notion usually called â€œmenâ€™s control of the dominant discourseâ€ in Beauvoir's words. There are some keys in the story showing that women are not satisfied with their ways of lives and try to change their current situation.